DOI: 10.54337/aau432703538
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Challenges and Potentials of Working Design-Based in Educational Research

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one copy of any publication from the public portal for the purpose of private study or research. -You may not further distribute the material or use it for any profit-making activity or commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 131 publications
(382 reference statements)
0
3
0
Order By: Relevance
“…The present study is a part of the broader DBR study to develop design framework with accompanying design principles for the digital learning ecosystem in ICT engineering education at (see Mielikäinen, 2022; Mielikäinen et al, 2023). DBR was chosen because of its suitability for designing educational interventions (Design-Based Research Collective, 2003) and producing guiding design principles (Gundersen, 2021; van Den Akker, 1999) for complex and practical educational design problems (McKenney & Reeves, 2019, p. 6). In DBR, the iterative development of solutions to complex real-world educational problems provides a context for empirical research (McKenney & Reeves, 2012, p. 8).…”
Section: Methodsmentioning
confidence: 99%
“…The present study is a part of the broader DBR study to develop design framework with accompanying design principles for the digital learning ecosystem in ICT engineering education at (see Mielikäinen, 2022; Mielikäinen et al, 2023). DBR was chosen because of its suitability for designing educational interventions (Design-Based Research Collective, 2003) and producing guiding design principles (Gundersen, 2021; van Den Akker, 1999) for complex and practical educational design problems (McKenney & Reeves, 2019, p. 6). In DBR, the iterative development of solutions to complex real-world educational problems provides a context for empirical research (McKenney & Reeves, 2012, p. 8).…”
Section: Methodsmentioning
confidence: 99%
“…Each play type results in the formulation of four design principles; we draw on these 12 principles to propose four general principles that can encourage participation in play. Inspired by Baumgartner and Bell (2002), we end the paper by presenting a meta-analysis in which the design principles for creative play, role play and movement play are transformed into four generic design principles (Gundersen, 2021). Those principles can be applied by pedagogues when they want to design for play activities in school in order to facilitate the development of an inclusive play environment.…”
Section: 0mentioning
confidence: 99%
“…As noted in the introduction, we worked systematically with design principles in a process that had largely been untested in pedagogical research in Denmark (Gundersen, 2021). In the DBR approach, design principles constitute an important part of the process and guide the design in a certain direction in relation to form, practice, function, aesthetics and so on.…”
Section: Design Principlesmentioning
confidence: 99%
“…The importance of design principles has been emphasised by several DBR researchers, who suggest that they should serve to guide interventions and support the creation of new knowledge (van den Akker, 1999;Gundersen, 2021). Design principles should be articulated in order to transform theoretical assumptions into specific guidelines that may address specific technological affordances, teachers' pedagogical approaches, or scaffold specific student tasks.…”
Section: The Role Of Design Principles In Dbrmentioning
confidence: 99%
“…Design principles are probably the most prevalent term used to characterise the theoretical understanding developed through iterative processes of educational design research. However, Gundersen (2021) finds in his review of 45 DBR studies that only one study reported on the development of guiding principles into conclusive or refined principles.…”
Section: Introductionmentioning
confidence: 99%